Critical education as an attempt to question the dominant habitus through the educational system - Dominik Chojnowski (Studia z Teorii Wychowania)
In the article, I analyze the role of education in the prevailing system of neoliberal capitalism. On the one hand, it is used by the dominant culture characteristic for the upper classes to imprint appropriate ideological assumptions in the minds of students. On the other hand, there is strong resistance to the practices of subordination and implementation of the logic of the prevailing system. Illich's concept of deschooling society recognizes that compulsory education should be abolished. Critical educators such as Henry Giroux and Peter McLaren argue that the resistance present in the school testifies to the possibility of using the school to shape critical citizens capable of defending democracy. In my article, I argue that it is possible to partially free oneself from the logic of the dominant culture and to partially emancipate the habituses characteristic of the lower classes. However, it is not my goal to illustrate the ideas present in the theories under analysis by referring to specific examples in the field of a particular educational system.